COMPREHENSIVE EVALUATION OF INDIAN STANDARD CODES AND CURING APPROACHES FOR GEOPOLYMER CONCRETE - Tikotkar, Shweta; Sandbhor, Sayali; Kulkarni, Sanjay (Journal of Applied Engineering Science, 2026)
Geopolymer Concrete (GPC) is a sustainable alternative to Ordinary Portland Cement (OPC), reducing global CO₂ emissions by 8-10% using industrial by-products such as fly ash, slag, metakaolin and silica fume. This approach not only reduces landfill waste and environmental pollution but also aligns with global sustainability goals. Extensive research highlights the increased sustainability of GPC, which includes excellent resistance to chemical corrosion, fire and elevated temperatures, rapid strength development and long-term structural stability. This study undertakes a comprehensive review of the existing literature on GPC, with a special focus on the applicability of Indian Standard (IS) codes for mix design and optimization of curing methods. However, despite significant research progress, GPC remains excluded from building codes in many regions. Given the absence of a dedicated design code for GPC, the review evaluates standardized test protocols for fresh and hard properties tailored to India's climatic conditions. The data for this analysis were systematically extracted from the Scopus database and non-Scopus journals, providing a solid foundation for critical evaluation, presented in a consolidated way to give a clear and focused context. This study validates GPC as a sustainable alternative to conventional concrete in India. However, optimization of mix design parameters, curing methods and durability performance, along with standardized guidelines, is required for widespread adoption. These findings provide important insights for researchers and practitioners to develop environmentally friendly construction technologies.
Keywords: geopolymer concrete, concrete composite, indian standard code, mix design, curing